Indo + Caribbean: The Creation of a Culture – An exhibition review of the great experiment of Indian indenture - Kavyta Raghunandan (Journal of Indentureship and its Legacies, 2024)
The museum exhibition, Indo + Caribbean: The Creation of a Culture , which ran at the Museum of London Docklands, offers a captivating and insightful exploration of the rich heritage and diverse traditions of the Indo-Caribbean community. Through a combination of artefacts, personal miscellany, for example, jewellery, letters petitioning the government from planter Sir John Gladstone, contracts, shipping company records, postcards and papers from the Parliamentary Archives and artworks, the exhibition provides a decent, albeit not exhaustive, overview of the historical, cultural and social aspects of Indo-Caribbean identity.